“Origen Did Not Allow Interpreting Books”: Comments and Glosses in the 17th-Century East Slavic Translation of Baronius’ “Annales Ecclesiastici” - Novak, Maria (Slavistica Vilnensis, 2022)
The article examines marginalia in one of the East Slavic hand-written versions of “Annales Ecclesiastici” by Caesar Baronius (Russian State Library, f. 256, no. 16, 17th century) in comparison with the Latin original, the Polish translation of Piotr Skarga published in 1607, and other Slavic versions from the 17th–18th centuries. Marginal comments of the book apparatus were studied in a pragmatic aspect, which took into account the narrative impact on the reader; glosses were analyzed in terms of lexemes’ interaction, considering their various origins and stylistic status. The author comes to the conclusion that the historical narrative formed through comments has a profoundly original nature. In the analyzed manuscript, the comments do not always follow Skarga’s commentaries: in part, their contents are possibly influenced by the Latin original, and in part, they represent their own emphases and judgments. The linguistic analysis shows that the vocabulary of Polish or Ruthenian origin (both with Slavic and non-Slavic (Greek, Latin, and German) roots) is glossed widely but inconsistently. The words of Greek and Slavic origin, which may have explanatory functions, are stylistically associated with both the literary Old Church Slavonic tradition and business writing. Less often, Polonisms can themselves play the role of explanatory marginalia.
Keywords: “Annales Ecclesiastici” by Baronius; East Slavic translations; comment apparatus; lexical glosses